Bupi Yishen Formula Versus Losartan for Non-Diabetic Stage 4 Chronic Kidney Disease: A Randomized Controlled Trial - Mao, Wei; Yang, Nizhi; Zhang, Lei; Li, Chuang; Wu, Yifan; Ouyang, Wenwei; Xu, Peng; Zou, Chuan; Pei, Chunpeng; Shi, Wei; Zhan, Jihong; Yang, Hongtao; et al. (Frontiers in Pharmacology, 2021)
Chinese herbal medicine (CHM) might have benefits in patients with non-diabetic chronic kidney disease (CKD), but there is a lack of high-quality evidence, especially in CKD4. This study aimed to assess the efficacy and safety of Bupi Yishen Formula (BYF) vs. losartan in patients with non-diabetic CKD4. This trial was a multicenter, double-blind, double-dummy, randomized controlled trial that was carried out from 11-08-2011 to 07-20-2015. Patients were assigned (1:1) to receive either BYF or losartan for 48 weeks. The primary outcome was the change in the slope of the estimated glomerular filtration rate (eGFR) over 48 weeks. The secondary outcomes were the composite of end-stage kidney disease, death, doubling of serum creatinine, stroke, and cardiovascular events. A total of 567 patients were randomized to BYF (n=283) or losartan (n=284); of these, 549 patients were included in the final analysis. The BYF group had a slower renal function decline particularly prior to 12 weeks over the 48-week duration (between-group mean difference of eGFR slopes: -2.25 mL/min/1.73 m2/year, 95% confidence interval [CI]: -4.03,-0.47), and a lower risk of composite outcome (adjusted hazard ratio=0.61, 95%CI: 0.44,0.85). Significant beneficial effects of BYF on the composite endpoint were observed in older patients (>45 years) and those with either hypertension or hyperuricemia. No significant between-group differences were observed in the incidence of adverse events. We may conclue that BYF might have renoprotective effects among non-diabetic patients with CKD4 in the first 12 weeks and over 48 weeks, but longer follow-up is required to evaluate the long-term effects.